2017
DOI: 10.1158/1078-0432.ccr-16-0303
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Methylation-Induced Loss of miR-181a2/181b2 within chr9q33.3 Facilitates Tumor Growth of Cervical Cancer through the PIK3R3/Akt/FoxO Signaling Pathway

Abstract: Purpose: Loss of Chr9q31-33 is one of the most common chromosome imbalances of cervical cancer, but the underlying mechanism has not been well documented.Experimental Design: The loss of heterozygosity (LOH) status of Chr9q31-33 was investigated utilizing 26 microsatellite markers. We detected the expression of miR-181a2/181b2 by qRT-PCR analysis of cervical cancer cell lines and 100 paired tumor samples and corresponding adjacent non-tumor tissues. Kaplan-Meier and Cox proportional hazard regression analyses … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 38 publications
(47 reference statements)
1
28
0
Order By: Relevance
“…The gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses were performed based on the top 10 differentially expressed miRNAs. The quantification of miRNAs of the plasma samples of the other 42 patients using real‐time polymerase chain reaction was then conducted separately as described previously 33. The primers used are shown in Supporting Information Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…The gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses were performed based on the top 10 differentially expressed miRNAs. The quantification of miRNAs of the plasma samples of the other 42 patients using real‐time polymerase chain reaction was then conducted separately as described previously 33. The primers used are shown in Supporting Information Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the mutations of PIK3CA E542K and E545K promote glycolysis and proliferation of CC in vitro and vivo [212]. NBPF1, ARHGAP17, miR-99b, -181a2/181b2, -338, -383, -433 and -489, as well as LncRNA ANRIL, CRNDE, NEAT1 and LINC01305 are involved in the proliferation, invasion, autophagy or EMT via PI3K/AKT pathway [213][214][215][216][217][218][219][220][221][222][223][224]. Currently, only preclinical trials of PI3K inhibitor LY294002 has revealed it significantly radiosensitized CC cell lines in vitro and vivo [225,226], and the terminated clinical trials of AKT inhibitor GSK2141795 (NCT01958112, Table 3) has tried to display a novel treatment approach to patients of CC.…”
Section: Nct02240212mentioning
confidence: 99%
“…In terms of tumor-suppressive miRNAs, aberrant methylation in the cpG islands of their promoters, was demonstrated to be one of the most common epigenetic mechanisms that modulated their expression and biological function (2). A number of miRNAs, including miR-132, miR-148a, miR-107, miR-181 and miR-34, have been identified to be epigenetically silenced by the hypermethylation of cpG islands in/near the promoter region (3)(4)(5). However, miRNA methylation status in endometrial carcinoma (Ec) has not been comprehensively investigated.…”
Section: Introductionmentioning
confidence: 99%